1977
DOI: 10.1002/ijc.2910200616
|View full text |Cite
|
Sign up to set email alerts
|

C. Parvum immunotherapy of transplanted rat tumours

Abstract: C.parvum (Wellcome CN 6134) has been tested for tumour suppression against a range of syngeneically transplanted rat tumours, both carcinogen-induced and of spontaneous origin. Subcutaneous growth was not prevented by distant subcutaneous or intravenous injection of the preparation, although growth rates were sometimes depressed or accelerated. In contrast, C. parvum injected in admixture with tumour cells consistently suppressed their growth and with highly immunogenic tumours induced systemic tumour immunity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

1978
1978
1981
1981

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…The ability of IP1 C. parvum to inhibit the growth of solid tumor deposits growing in the pleural cavity in mice accords with similar findings for the rat where IP1 C. parvum has reduced both solid tumors and pleural effusions (Pimm and Baldwin, 1977). Pleural macrophages were both increased in number and highly activated after IP1 C. parvum and it is likely that these were responsible for local tumor destruction within the pleural cavity.…”
supporting
confidence: 83%
“…The ability of IP1 C. parvum to inhibit the growth of solid tumor deposits growing in the pleural cavity in mice accords with similar findings for the rat where IP1 C. parvum has reduced both solid tumors and pleural effusions (Pimm and Baldwin, 1977). Pleural macrophages were both increased in number and highly activated after IP1 C. parvum and it is likely that these were responsible for local tumor destruction within the pleural cavity.…”
supporting
confidence: 83%
“…Subcutaneous injection was ineffective, while intravenous injection, in one of two tests, markedly enhanced growth. Enhancement of tumour growth by Cparvum has been reported in other tumour systems, including the rat strain used in the present investigation (Pimm and Baldwin, 1977;Bomford, 1977), and although its mechanism is as yet not clear, the induction of suppressor cells by C.parvum has been reported by Kirchner et al (1975), while Bomford (1977) interprets enhancement of tumour growth as a reflection of the trapping of effector lymphocytes at the site of C.parvum injection. The mechanism of positive tumour suppression by systemically administered C.parvum, such as intradermal injection reported here, is regarded, like the local application of Cparvum, as primarily involving activation of host macrophages (Scott, 19746 Woodruff and Warner, 1977;Bjornsson eta/., 1978) although this question is not fully resolved in view of the more recent demonstration of enhanced normal killer (NK) cell activity as well as activated macrophages in Cparvum-and BCG-treated rats (Oehler and Herberman, 1978 ; Oehler et a/., 1978).…”
Section: Discussionmentioning
confidence: 56%
“…The objective of the present investigation was to extend these previous studies with Glaxo BCG in order t o examine the influence of C.parvum on the same range of five transplanted rat tumours, essentially to determine whether a better therapeutic response could be achieved with this agent. The C.parvum preparation used, Wellcome CN6134 (more correctly Propionibacteriurn acnes), has previously been shown to be effective against carcinogen-induced rat tumours (Pimm and Baldwin, 1977) and quantitative comparisons indicated that it was the superior of three C.parvum strains examined (Willmott et al, 1979~). Tests have also been carried out t o compare this C.parvum preparation with Pasteur and Connaught strains of BCG, since more recent studies indicate that these are quantitatively superior to Glaxo BCG in suppressing carcinogeninduced rat sarcomas (Willmott et a/., 1979b).…”
mentioning
confidence: 99%
“…It is important to note that the EL-4 lymphoma is of low immunogenicity and rapidly progresses, resulting in quick death of the animals [9,14]. Previous experiments have similarly demonstrated that bacterial therapy of less immunogenic, rapidly developing rat tumors resulted in survival of the animals, but in no demonstrable systemic immunity [23]. In those experiments, groups of animals which had rejected mixed subcutaneous inocula of various tumor cells and C. parvum were challenged with tumor cells alone.…”
Section: Discussionmentioning
confidence: 90%
“…The beneficial effects of Mycobacterium boris ( B C G ) and Propionibacterium acnes (Corynebacterium parvum) upon the course and development of a variety of transplantable animal tumors, as well as upon certain h u m a n tumors has been well documented [1,2,7,10,16,18,23,25,30]. In addition to these two bacteria, several other micro-organisms have been shown to exert significant antitumor effects in a n u m b e r of diverse experimental systems [3,4,8,11,22,29].…”
Section: Introductionmentioning
confidence: 98%